Analysis of the characterization of the adhesion property in intermediate layers of asphalt pavement - Povis Condor, Kevin Antony (2025)
The present study analyzes the characterization of adhesion properties in intermediate layers of asphalt pavement, a critical factor influencing road durability and performance. The research is based on a systematic review of scientific literature, highlighting different methodologies for evaluating interlayer bonding, experimental tests, and international standards such as AASHTO, ASTM, and MTC regulations. A comparative analysis was conducted between samples obtained from the “Improvement of the Santa Maria - Santa Teresa - Hydroelectric Machu Picchu Bridge Road” project and laboratory simulations using the LOTTMAN test. The results demonstrate that the amount of tack coat significantly affects interlayer adhesion. Experimental tests confirmed that a tack coat application rate of 0.4 l/m² provides optimal indirect tensile strength (TSR) values, improving mechanical bonding between asphalt layers. Moreover, findings indicate discrepancies between laboratory simulations and real-world construction data, emphasizing the need for field verification to ensure adherence to project specifications. The study concludes that optimizing tack coat application techniques is crucial for enhancing pavement structural integrity. Future research should focus on refining non-destructive testing methods, such as the Falling Weight Deflectometer (FWD), to evaluate interlayer adhesion in situ. Establishing standardized adhesion evaluation protocols will contribute to more durable and cost-effective pavement infrastructure.